Problematika dan Prospek Pengaturan Proses Hukum Penganan Perkara Koneksitas - Saragih, Indra Aprio Handry (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2024)
Since the enactment of Joint Decision Number KEP/B/61/XII/1971, the Criminal Procedure Code (KUHAP) and the Military Judiciary Law, which regulate the legal process for handling connectivity cases, most connectivity cases have not been processed as connectivity cases. This research is normative legal research related to the systematics of law with a legislative approach. The results of this research indicate that the failure to implement connectivity according to KUHAP and the Military Judiciary Law is due to the connectivity norms being lex imperfecta, meaning that if these norms are not implemented, there are no sanctions for law enforcement officers. The central role of the prosecution in handling connectivity cases is granted by law to the Attorney General to coordinate, control, and conduct investigations, inquiries, and prosecutions of criminal acts committed jointly by civilians and military personnel. The Attorney General delegates part of the prosecutorial authority to the General Auditor for prosecution purposes. This is the embodiment of the dominus litis principle and the single prosecution system, which means that all prosecutorial authority is under the supervision and control of the Attorney General as the highest public prosecutor, especially within the new structure of the Military Criminal Attorney General. The Military Criminal Attorney General has duties and authority in the technical coordination of prosecution in handling connectivity cases and acts as a catalyst in handling connectivity cases through connectivity examination procedures.